Isolated and combined effect of lead nanoparticles and lead acetate with sodium and potassium stearates at peroral intake into organism - Kondratiuk, V.A.; Fedoriv, O.Ye.; Lototska, O.V. (Environment & Health, 2016)
Objective. We studied a character of isolated and combined effect of lead nanoparticles and lead acetate with sodium and potassium stearates under conditions of their intake with drinking water into organism. Materials and methods. We used hygienic, toxicological, biochemical, morphological, hematological and statistical methods (Student t-test, Mann-Whitney test), correlation analysis, divisional and additive options for the calculation of the coefficient of joint effect in terms of central tendency, variability and assessments of probability after M.Yu. Antomonov. Results. Under conditions of acute sanitary-and-toxicological experiment LD50 of lead acetate and lead nanoparticles was established to manifest a similar toxicity, to be at the level of 294.0 (242.0 ÷ 346.0) mg / kg (toxicity grade 1) and to have a pronounced capacity for cumulation (CI = 0.7). Maximum non-affecting concentration was ascertained to be equal to 0.006 mg/dm3, adjusted for the grade of toxicity - 0.0006 mg/dm3. A tentatively safe level for potassium stearate is 0.25 mg/dm3, for sodium stearate - 0.16 mg/dm3 on the basis of general sanitary hazard sign at the control of water quality for domestic-drinking and cultural-and-residential use. The combined effect of nanoparticles and lead acetate at the peroral use of drinking water with sodium and potassium stearates causes leukocytosis, accelerated maturation of myeloid series of cells in a bone marrow of rats and arrest of their release into peripheral blood due to inefficient cell division pronounced vascular disorders in liver, dystrophic, necrobiotic changes of hepatocytes, connective tissue cells, stromal cell infiltration. Less pronounced changes in the test body structure took place at the combined effect of lead acetate with sodium stearate.